FeTPPS Reduces Secondary Damage and Improves Neurobehavioral Functions after Traumatic Brain Injury - Bruschetta, Giuseppe; Impellizzeri, Daniela; Campolo, Michela; Casili, Giovanna; Di Paola, Rosanna; Paterniti, Irene; Esposito, Emanuela; Cuzzocrea, Salvatore (Frontiers in Neuroscience, 2017)
Traumatic brain injury (TBI) determinate a cascade of events that rapidly lead to neuron’s damage and death. We already reported that administration of FeTPPS, a 5,10,15,20-tetrakis (4-sulfonatophenyl) porphyrin iron III chloride peroxynitrite decomposition catalyst, possessed evident neuroprotective effects in a experimental model of spinal cord damage. The present study evaluated the neuroprotective property of FeTPPS in TBI, using a clinically validated model of TBI, the controlled cortical impact injury (CCI). We observe that treatment with FeTPPS (30 mg/kg, i.p.) reduced: the state of brain inflammation and the tissue hurt (histological score), myeloperoxidase activity, nitric oxide production, glial fibrillary acidic protein (GFAP) and pro-inflammatory cytokines expression and apoptosis process. Moreover, treatment with FeTPPS re-established motor-cognitive function after CCI and it resulted in a reduction of lesion volumes. Our results established that FeTPPS treatment decreases the growth of inflammatory process and the tissue injury associated with TBI. Thus our study confirmed the neuroprotective role of FeTPPS treatment on TBI.